Enhancing Students’ Writing Skill Through Threads Application in SILC (Skapsa International Language Class) at Kediri - Wahyuni, Sri; Fahruriza, Syahrul Erva; Ningrum, Ary setya Budhi (Proceeding International Conference on Education, 2025)
Writing is an essential skill yet hard to be master especially for EFL students. There are some challenges in writing such as vocabulary mastery, generating ideas, transforming ideas in to a text. To address students’ challenges in writing, this study proposed Threads application to help them to write better. It is a text-based social media platform developed by Meta for Instagram users, allowing users to post, comment, and share ideas. This study aimed to enhance students’ writing exposition text skills in SILC (SKAPSA International Language Class) at Kediri. In this study, classroom action research (CAR) approach was employed as the research design. One class consisting of eighteen students of SKAPSA (SMK PGRI I Kediri) participated in this study. The research was conducted in two cycles, and each cycle consists of three meetings. The data were collected through observation and writing tests. The criteria of success included an average score at least 75, and 85% of students passed the Minimum Competency Standards (KKM). The results showed good improvement. In the preliminary test, the average score was 60.22, with only 22.22% passing grade. After implementation of Threads in cycle I, the average rose to 75.5 (61.1% passing grade), and in cycle II, it rose to 80.1 with 94.4% passing grade. It can be concluded that Thread application can enhance the students’ writing skill.  Therefore, it is suggested for EFL teachers to use Threads application as an alternative technology based application to enhance students’ learning especially in writing.